2019
DOI: 10.30519/ahtr.468484
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Satisfaction for American Aesthetic Tourism at the Mexican Border

Abstract: The aim of this study was to find out the predictors for aesthetic tourism patients´ satisfaction of the American travelers to Tijuana. The information was obtained by applying a survey to a sample of 385 visitors-patients from clinics in the city. Four dimensions were included in the multiple regression analysis. The results obtained show that the two key factors influence satisfaction level: Medical facilities, services and price dimension, and Geographical and cultural proximity dimensions. Theoretical valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Identifying the concerns and factors affect the satisfaction and acceptance of citizens in a health tourism destination, along with paying attention to the main product, which provide health services for health tourists, and trying to address these concerns and eliminate the factors causing concern among citizens can be a factor in creating an advantage for a health tourism destination. 21 The results of the present study indicated that the citizens of a health tourism destination are not passive towards the development of this industry in their place of residence and taking into account the individual and social interests perceived by themselves and relatives, they will have a reaction on this issue and its consequences.…”
Section: Discussionmentioning
confidence: 63%
“…Identifying the concerns and factors affect the satisfaction and acceptance of citizens in a health tourism destination, along with paying attention to the main product, which provide health services for health tourists, and trying to address these concerns and eliminate the factors causing concern among citizens can be a factor in creating an advantage for a health tourism destination. 21 The results of the present study indicated that the citizens of a health tourism destination are not passive towards the development of this industry in their place of residence and taking into account the individual and social interests perceived by themselves and relatives, they will have a reaction on this issue and its consequences.…”
Section: Discussionmentioning
confidence: 63%
“…Likewise, the US-Mexico border has featured prominently in the international media over illegal immigration and the US government's responses to it (Gravelle, 2018). These happenings have reduced the contemporary appeal of the borderlands as a leisure tourist destination, but they remain some of the most visited parts of Mexico (Toudert & Bringas-Rábago, 2018;Ramos & Cuamea, 2019), primarily for 'medical tourism' services.…”
Section: Tourism and The Usa-mexico Bordermentioning
confidence: 99%